Implantação do Fundo do Idoso no município de São Paulo: proposta para estruturação e gestão - Cunha, Rosana Paulo da (2015)
This dissertation has been drawn up taking as an object of study the implementation of the Elderly Fund the city of São Paulo, created by Law No. 15.679, of December 21, 2012, and the production of a proposal for structuring and management. This is an important mechanism that allows the city of São Paulo to receive resources of the respective federal and state funds, fines arising from lawsuits or terms of conduct adjustment regarding situations of violations of elderly rights, and even donations from natural or legal person deductible from income tax. The study was undertaken aiming to understand the situation of the elderly in the country and particularly in the city of São Paulo – place where the elderly fund resources will be used – their demands and major violations of their rights, the situation of public policy directed at the elderly in the city from the observance of the current management goals plan, identifying key players of the elderly policy in the city, the identification of a paradigmatic fund - in this case of Porto Alegre - that would allow us to foresee possible problems, challenges and the way that managers have overcome obstacles, all in order to formulate a proposal which aimed at this reconstructed scenario. Furthermore, it was surveyed which cities with population above 500 (Five hundred) thousand inhabitants who have elderly fund, and how they are structured so that future studies can avail themselves of this data in a more comparative work. Moreover, we sought to identify the problems and challenges in the Fund for Children and Adolescents in the city of São Paulo, managed by the Municipal Bureau of Human Rights, which will also be the manager of the Elderly Fund in the city when regulated, as means of avoiding the same problems from recurring in the elderly fund. The authors concluded - based on an analysis of all documentation, perceptions and expectations of the actors involved - that despite the difficulties of implementation and management - resulting from the absence of structure, quantity and qualification of personnel and infrastructure - the referred elderly fund can contribute significantly to the development of new projects in the city, mobilizing additional resources from non-budgetary resources and contribute to a better qualification of the set of policies aimed at the elderly population. Finally, as part of this work, we propose a draft regulatory.